Productivity income nexus in Nigeria: Empirical lessons from COVID-19 lockdown - N.A. Sofoluwe; L.A. Odusanya; O.G. Yinusa; L.O. Oyelami; S.O. Adeyemo (Ruhuna Journal of Science)
In an attempt to control the coronavirus, governments worldwide imposed lockdown measures, yet the consequences on productivity income for microeconomic policy were not clearly known, especially in developing countries. This study examined the effect of the COVID-19 pandemic on the productivity and income of Nigerian households under strict lockdown during 2020 using a cross-section based online survey. Participants were sampled from Nigeria’s geopolitical zones via a snowball sampling method. A total of 467 household data were utilized for the analysis. Descriptive statistics, hierarchical and stepwise regression models were applied to the data. Results show that the COVID-19 lockdown negatively affected productivity by 71.3% and income by 58.2%. Younger populations were more affected (β = -0.159, p<0.05) as well as people with marital responsibilities (β = 0.617, p<0.05). The global pandemic had negative consequences on the productivity of young populations. The reducing effect of the pandemic on income had the potential to add a greater burden to the household welfare of family people. This study provides an empirical insight into the microeconomic effect of a pandemic on households in developing nations.